Hubungan Antara Efikasi Diri dengan Beban Kognitif Siswa SMP Muhammadiyah 1 Sidoarjo: Correlation Between Self Efficacy and Cognitive Load In Junior High School Muhammadiyah 1 Sidoarjo - Defta Innayah Herliyanti; Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Cognitive load represents the mental effort experienced by students during learning activities and is closely related to working memory capacity. Specific Background: Junior high school students often encounter complex academic demands that may generate cognitive load, while psychological factors such as self-efficacy are assumed to be associated with students’ mental processing during learning. Knowledge Gap: Previous studies have examined cognitive load in various contexts; however, empirical evidence linking self-efficacy and cognitive load among junior high school students remains limited. Aims: This study aims to determine the relationship between self-efficacy and cognitive load among students of Muhammadiyah 1 Sidoarjo Junior High School. Results: Using a quantitative correlational design with 221 students selected through stratified random sampling, data analysis with Pearson correlation revealed a positive and significant relationship (r = 0.510; p < .001). The coefficient of determination indicated that self-efficacy contributed 26% to cognitive load variance. Novelty: This study provides empirical evidence on the positive correlation between self-efficacy and cognitive load within the context of junior high school students. Implications: The findings contribute to educational psychology by highlighting the role of students’ belief systems in relation to mental workload during learning processes. Keywords: Self Efficacy, Cognitive Load, Junior High School Students, Educational Psychology, Pearson Correlation Key Findings Highlights: A moderate positive correlation was identified between the two measured constructs. The independent variable accounted for 26% of variance in the dependent variable. Most participants were categorized within the moderate level for both measured variables.